Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. Research priorities in the administration of public education in The Kingdom of Saudi ArabiaDr. Manal Abdulaziz Alsalem,Mrs. Mashael Saleh Aljuwayid, Mrs. Mashael Mohammed Alghurayr2. Determinants of selecting the national wrestling team juniors in training centers in the capital, Sana'aMr. Kamal Muhammad Al-Taweel, Prof. Ibrahim Ali Al-Warafi3. The impact of transformational leadership on the decision-making process in secondary schools  in TabukMr. Fahad A. Albalawi4. The reality of application administrative governance at King Abdulaziz University  from point of view of teaching faculty membersMrs. Mona Mohammed Alzahrani, Dr. Omar Mohammed Badawood5. The effectiveness of a proposed training program based on an adaptive e-learning environment  in developing productive thinking skills among productive families in JeddahMrs. Hanin Muhammad Zuhair Najjar, Prof. Suhail Salem Al-Harbi6. Priorities of Appropriate Intervention to Empowering People with Developmental Disorders  and Integrate them into Social Life from the Point of View of their FamiliesMrs. Amani O. Abuzahera7. The Extent of Undergraduate Student Participation in Conducting Scientific Research  at The University of Nizwa in the Sultanate of OmanDr. Radhiya Sulaiman Al-Habsi , Mrs. Ikram Hamad Ali Al-Maadi , Mr. Ammar Saeed Amer Al-Salmani
Keywords: Journal of Educational and Psychological Sciences